Development Of Simulation Program For Thermal Energy Storage Integrated District Cooling System - Abd Salam, Amir ihsan (2002)
Awareness on the environment and significant benefit to the customer has lead to the growth of Thermal Energy Storage (TES) application in Malaysia. Most of them are implemented in medium to large chilled water manufacturing facility that cooled multiple buildings in a widespread area or integrated in a District Cooling System (DCS). For encapsulated ice method, the difference in the amount of ice supplied to supplement the chilled water generated during peak hours plays major role in ascertaining the result of electricity bill savings and therefore, payback period. Based on actual implementation in Cyberjaya, Selangor, a simple simulation program of TES integrated DCS is created to study the impact on the electricity bill savings,conventional system. Varying the percentage of ice supply, application to cooling capacity of 500 RT, 1000 RT, 1500 RT with and without base load, on different tariff rates are calculated. It shows that integration of smallest percentage of TES is most feasible in terms of payback period and electricity consumption. However, the amount of savings is small. As the ice making process operates at lower temperature, there is also penalty on energy consumption. On tariff imposed, the acceptable range for base load and percentage of ice supply that is feasible are identified while most of the rates in no base condition qualify to entitlement of payback period under five years. The parameters whereby TES integrated DCS are not advisable are also acknowledged.